Cryptic inhibitory regions nearby activation domains - Knight, Andrea; Piskacek, Martin (Biochimie, 2022)
Previously, the Nine amino acid TransActivation Domain (9aaTAD) was identified in the Gal4 region 862-870 (DDVYNYLFD). Here, we identified 9aaTADs in the distal Gal4 orthologs by our prediction algorithm and found their conservation in the family. The 9aaTAD function as strong activators was demonstrated. We identified adjacent Gal4 region 871-811 (DEDTPPNPKKE) as a natural 9aaTAD inhibitory domain located at the extreme Gal4 terminus. Moreover, we identified conserved Gal4 region 172-185 (FDWSEEDDMSDGLP), which was capable to reverse the 9aaTAD inhibition. In conclusion, our results uncover the existence of the cryptic inhibitory domains, which need to be carefully implemented in all functional studies with transcription factors to avoid incorrect conclusions.
Keywords: DNA vazebné proteiny; sekvence aminokyselin; Saccharomyces cerevisiae - proteiny; DNA-Binding Proteins; Saccharomyces cerevisiae Proteins; Transcription Factors; transkripční faktory; Transcriptional Activation; Amino Acid Sequence; aktivace transkripce